2012
DOI: 10.1155/2012/120702
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Valve Regurgitation after Orthotopic Heart Transplantation: Prevalence and Etiology

Abstract: Background. Tricuspid valve regurgitation (TR) after orthotopic heart transplantation (OHT) is common. The aims of this study were to determine the prevalence of TR after OHT, to examine the correlation between its development and various variables, and to determine its outcomes. Methods. All 163 OHT patients who were followed up between 1988 and 2009 for a minimal period of 12 months were divided into those with no TR/mild TR and those with at least mild-moderate TR, as assessed by doppler echocardiography. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
2
16
0
3
Order By: Relevance
“…The exact etiology of TV regurgitation after OHT is unknown. Anastomotic technique, donor/recipient size characteristics, number of cellular rejections, and iatrogenic injury during endomyocardial biopsies have all been implicated (9). TR at the time of OHT has been shown to predict poor late survival, though it is unclear if TV interventions at the time of OHT will improve long-term outcomes (10).…”
Section: Discussionmentioning
confidence: 99%
“…The exact etiology of TV regurgitation after OHT is unknown. Anastomotic technique, donor/recipient size characteristics, number of cellular rejections, and iatrogenic injury during endomyocardial biopsies have all been implicated (9). TR at the time of OHT has been shown to predict poor late survival, though it is unclear if TV interventions at the time of OHT will improve long-term outcomes (10).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that the majority of TVR that develops following heart transplantation does not lead to symptoms significant enough to warrant surgical repair (2,4,6). In the minority of patients, however, for whom TVR leads to medically refractory symptoms, repair and replacement options have been employed.…”
Section: Surgical Indications For Tricuspid Valve Repair or Replacementmentioning
confidence: 99%
“…Berger et al провели сравнительный анализ результатов трансплантации сердца у пациентов, перенесших операцию, выполненную по биатриаль-ной и бикавальной методикам. В ходе исследования было выявлено, что у 65% реципиентов со средней и тяжелой степенью регургитации трикуспидального клапана была выполнена трансплантация по биатри-альной методике [29].…”
Section: хирургическая методика трансплантации сердцаunclassified
“…Berger et al в своем исследовании обнаружили статистически значимую корреляцию между высокой степенью легочной гипертензии в дооперационном периоде и развитием на трикуспидальном клапане регургитации после операции [29].…”
Section: легочная гипертензия и высокое сосудистое сопротивлениеunclassified
See 1 more Smart Citation